The First Attend for a Holistic HBIM Documentation of UNESCO WHL Monument: The Case Study of Asinou Church in Cyprus - Themistocleous, Kyriacos; Ioannides, Marinos; Georgiou, Simos; Athanasiou, Vasilis (My University, 2018)
The study examines the documentation of the Asinou Monument within the auspices of the H2020-SC6-R&I-INCEPTION project. The project focuses on the use of innovative 3D modelling of cultural heritage through an inclusive approach for 3D reconstruction of monuments, as well as the built and social environments over time. The project will enrich European identity by examining how European cultural heritage evolves over time. Therefore, data acquisition techniques and 3D reconstruction and modelling methodologies for data processing were examined using the Asinou Church as a case study. Asinou Church is a 11th century church located in the Troodos Mountains of Cyprus, which is a UNESCO World Heritage Site. This unique monument contains some of the finest Byzantine wall paintings in Cyprus which date between the 11th to the 17th century. Their outstanding historical value is very exceptional and makes their documentation a great challenge for the present ICT technologies. Different multimodal techniques, such as photogrammetry, laser scanning, image processing, video and audio were used for the data acquisition of all detailed features of the tangible building and the intangible story (liturgy). Following, the information was processed to create a 3D model in order to document the church using Building Information Modeling (BIM). The church was digitally reconstructed in a 3D BIM model, where it was then processed to produce a Heritage Building Information Model (H-BIM) in order to create a prototype for a holistic documentation and further study.
Keywords: 3D model; 3D reconstruction; Asinou Church; BIM; Digital cultural heritage; EU-H2020 INCEPTION; H-BIM; Remote sensing; UNESCO WHL